Soluble and Perfluorinated Polyelectrolyte for Safe and High‐Performance Li−O2 Batteries - Xiong, Qi; Huang, Gang; Yu, Yue; Li, Chao‐Le; Li, Jian‐Chen; Yan, Jun‐Min; Zhang, Xin‐Bo (Angewandte Chemie International Edition, 2022)
The severe performance degradation of high‐capacity Li−O2 batteries induced by Li dendrite growth and concentration polarization from the low Li+ transfer number of conventional electrolytes hinder their practical applications. Herein, lithiated Nafion (LN) with the sulfonic group immobilized on the perfluorinated backbone has been designed as a soluble lithium salt for preparing a less flammable polyelectrolyte solution, which not only simultaneously achieves a high Li+ transfer number (0.84) and conductivity (2.5 mS cm−1), but also the perfluorinated anion of LN produces a LiF‐rich SEI for protecting the Li anode from dendrite growth. Thus, the Li−O2 battery with a LN‐based electrolyte achieves an all‐round performance improvement, like low charge overpotential (0.18 V), large discharge capacity (9508 mAh g−1), and excellent cycling performance (225 cycles). Besides, the fabricated pouch‐type Li–air cells exhibit promising applications to power electronic equipment with satisfactory safety. A novel design principle of polymerization and fluorination for salt anions has been proposed and lithiated Nafion (LN) was suggested as a representative soluble lithium salt for the polyelectrolyte solution to improve the Li+ transfer number and produce a LiF‐rich solid electrolyte interface (SEI). Furthermore, the perfluorinated backbone of LN delivers the polyelectrolyte solution low flammability. Thus, making the Li−O2 batteries realize all‐round performance amelioration.